KEPEMIMPINAN KEPALA SEKOLAH DALAM PEMBUATAN LAYANGAN UNTUK MENUMBUHKAN JIWA KREATIVITAS DAN KEWIRAUSAHAAN BAGI SISWA DI SDN 02 TELAGA BIRU - Muharlin Syah; Nana Erlina S Humonggi; Nur Vadilla Katili; Indira Oktaviyani Badaru; Abdul Rahmat; Isnanto Isnanto (Asosiasi Dosen Muda Indonesia, 2022)
The principal is a position that has great responsibility for determining the direction of school goals. The principal is expected to be able to carry out his responsibilities to carry out the vision and mission set by the school which is the main goal of establishing a school. In accordance with Permendiknas NO 13 of 2007 school principals have several competencies that must be possessed, one of which is entrepreneurial competency. So that the principal must be able to create entrepreneurship that can be applied and carried out by students at school. One type of entrepreneurship that can be applied to elementary school children is making kites as a tool for entrepreneurship. Besides being close to children, kite is a game that is close to all elements of society, from children to adults can play kites. Besides that, kites are also games that have cultural values, so they are very suitable to be used as a means of entrepreneurship for elementary school children to be able to foster a spirit of creativity and entrepreneurship.